1994
DOI: 10.1111/j.1440-169x.1994.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrastructural Investigation on Vitellophage Invasion of the Yolk Mass during and after Germ Band Formation in Embryos of the Stick Insect Carausius morosus Br.

Abstract: Developing embryos of the stick insect Carausius morosus were examined ultrastructurally with a view to studying vitellophage invasion of the yolk mass during and after germ band formation. Newly laid eggs in Cmorosus have a unique yolk fluid compartment surrounded by a narrow fringe of cytoplasm comprising several small yolk granules. Vitellophages originate mainly from a thin layer of stem cells, the so-called yolk cell membrane, interposed between the germ band and the yolk mass. Throughout development, a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Portions are engulfed and sequestered as large vacuoles (56) in a sequence of events strikingly similar to that observed in embryogenesis of the stick insect Carausius morosus Br. (57). The B. germanica vacuoles then become vesiculated and partitioned into smaller vesicles (56) with the same size distribution as granules isolated from yolk (20).…”
Section: Discussionmentioning
confidence: 99%
“…Portions are engulfed and sequestered as large vacuoles (56) in a sequence of events strikingly similar to that observed in embryogenesis of the stick insect Carausius morosus Br. (57). The B. germanica vacuoles then become vesiculated and partitioned into smaller vesicles (56) with the same size distribution as granules isolated from yolk (20).…”
Section: Discussionmentioning
confidence: 99%
“…For scanning electron-microscopic observations, yolk sacs were dissected in phosphate-buffered saline (PBS) and fixed in Karnovsky's fixative as previously reported (Fausto et al 1994). They were then thoroughly rinsed in 0.1 M cacodylate buffer at pH 7.2, postfixed for 2 h in 1% osmium tetroxide in 0.1 M cacodylate buffer at pH 7.2, dehydrated in an ascending series of alcohols and eventually critical point dried in a Balzer's apparatus equipped with a liquid CO 2 inlet.…”
Section: Structural Observationsmentioning
confidence: 99%
“…We have studied yolk utilisation in embryos of the stick insect Carausius morosus and found that yolk granules in this species are reconstituted anew with the beginning of embryonic development (Fausto et al 1994). By this time, the fluid ooplasm is gradually transformed into a collection of progressively smaller yolk granules due to invasion of secondary vitellophages from the egg periphery (Fausto et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Yolk sacs were fixed in Karnovsky's fixative as previously reported (Fausto et al 1994). They were thoroughly rinsed in 0.1 M cacodylate buffer at pH 7.2, postfixed for an additional 2 h in 1% osmium tetroxide in 0.1 M cacodylate buffer at pH 7.2, dehydrated in an ascending series of alcohols, embedded in Epon-Araldite and allowed to polymerize for 3 days at 60°C.…”
Section: Structural Observationsmentioning
confidence: 99%
“…In hemimetabolous insects, embryos develop from a ventral thickening of the peripheral blastoderm, the so-called germ band, while the extra-embryonic blastoderm differentiates into such membranous envelopes as the inner amnion and the outer serosa membrane (Campos-Ortega & Hartenstein 1985;Pennacchio et al 1994). Newly laid eggs of the stick insect Carausius morosus are characterized by a yolk fluid ooplasm, which is partitioned into a number of yolk granules on invasion of secondary vitellophages from the egg periphery (Fausto et al 1994). A morphologically similar process appears to occur in other orthopteroid species (Petavy 1985;Giorgi & Nordin 1994).…”
Section: Introductionmentioning
confidence: 99%